(3CQcGf hVeGfGJ GdMce GdGSdGej (B/s - (3eaJj , eMeO CMeOs (Beirut : Mu'assasah al-Rayan, 1996)
Modern treatise on the principles & guarantees of Islamic government, by a Saudi academic
Keywords: Islam and state